Earned Value Management System in Manufacturing Industry / Fatemeh Rasooli Haghighi - Fatemeh, Rasooli Haghighi (2013)
Project management is the act of planning, organizing, motivating and controlling resources of time and cost to achieve specific goals known as scope of project. Earned Value Management (EVM) or Earned Value Project/Performance Management (EVPM) is a project management technique that measures project progress and performance in an objective manner and provide accurate forecast of project performance problem (Marshall 2006). EVM is widely accepted in many manufacturing projects in developed countries such as the USA, UK and Australia (Garrett,2006). EVM is not classified as a common used tool in manufacturing industry sector in Malaysia (Khamidi, Ali et al. 2011). This study will discuss the technique of EVM, a method of evaluating and measuring project performance and progress, which is known as one of the most accurate and sharp managing techniques (Vandevoorde and Vanhoucke 2006, Moslemi Naeni, Shadrokh et al. 2013). According to Anbari (2003), EVM is a powerful method of project management and handling that supports cost, time and scope of project. Brandon & Daniel,1998 also introduced EVM as a powerful technique of true project performance measurement. In order to practically demonstrate the effectiveness of EVM on manufacturing project management and how obtained result from EVM implementation would help project managers in project forecast and management in manufacturing sector, EVM is implemented on a manufacturing project producing safety glasses for automobile industry in Malaysia. The aim of this work is to show that how EVM can be applied to Malaysian manufacturing projects. The results obtained from successful implementation of EVM on purposed manufacturing project demonstrated that EVM can bring a very clear view of the project and provide project managers strong insight into the project progress. This technique would enable project managers to assess project performance more in-depth and vi help project managers to effectively control, monitor and manage project cost and schedule. Moreover EVM facilitates project managers with a very good prediction of future performance trend of the project. Keywords: Project Management, Earned Value Management (EVM), Project Performance Measurement, Forecast Project Performance Problem, Manufacturing Project Management